2005
DOI: 10.4049/jimmunol.174.7.4120
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Acts as a Soluble Host Factor That Promotes HIV-1 Infectivity through Stabilization of Virus Attachment to Host Cells

Abstract: The establishment of HIV type 1 (HIV-1) infection is initiated by the stable attachment of the virion to the target cell surface. Although this process relies primarily upon interaction between virus-encoded gp120 and cell surface CD4, a number of distinct interactions influence binding of HIV-1 to host cells. In this study, we report that galectin-1, a dimeric β-galactoside-binding protein, promotes infection with R5, X4, and R5X4 variants. Galectin-1 acts as a soluble adhesion molecule by facilitating attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 48 publications
(61 reference statements)
2
162
1
5
Order By: Relevance
“…On the surface of T lymphocytes, galectin-3 lattices are suggested to restrict T cell receptor recruitment to the site of antigen presentation, thereby increasing the threshold for T lymphocyte activation (47). We recently found that galectin-3 interferes with the galectin-1-mediated promotion of human immunodeficiency virus attachment and infectivity in CD4 T lymphocytes even though galectin-3 alone does not have any of those activities (59). Thus, the robustness of galectin-3 lattices revealed by the FRAP technique might contribute to the various regulatory functions of galectin-3 lattices.…”
Section: Discussionmentioning
confidence: 99%
“…On the surface of T lymphocytes, galectin-3 lattices are suggested to restrict T cell receptor recruitment to the site of antigen presentation, thereby increasing the threshold for T lymphocyte activation (47). We recently found that galectin-3 interferes with the galectin-1-mediated promotion of human immunodeficiency virus attachment and infectivity in CD4 T lymphocytes even though galectin-3 alone does not have any of those activities (59). Thus, the robustness of galectin-3 lattices revealed by the FRAP technique might contribute to the various regulatory functions of galectin-3 lattices.…”
Section: Discussionmentioning
confidence: 99%
“…However, galectin-1 can also promote human immunodeficiency virus infectivity by stabilizing viral attachment to host cells and cross-linking viral glycoproteins with the target cells [28]. Specific interactions have been described between galectin-3 and -9 and the intracellular protozoan Leishmania.…”
Section: Galectin-carbohydrate Lattices In Host-pathogen Interactionsmentioning
confidence: 99%
“…Galectins are PRRs in several types of organisms, and many mammalian pathogens express saccharide structures that are recognized by galectins. Galectin-1 binds saccharide ligands on envelope glycoproteins of Nipah virus and HIV (20,21). Galectin-3 and galectin-9 bind Leishmania major and galectin-9 promotes L. major-macrophage interactions (22,23).…”
mentioning
confidence: 99%